(untitled) (The Asian Journal of Technology Management (AJTM), 2017)
Abstract: During recent years the concept of farmer empowerment has been put on the agenda and now is a part of Indonesianâ€™s government program. Empowerment of farmersâ€™ group considered necessary because, in agricultural development, farmersâ€™ group are the key development resource and subject in developing their agricultural efforts. This paper aims to explore the farmerâ€™s group empowerment strategies to improve their income. The paper is based solely on the reviews of literature on the topic of farmerâ€™s group and empowerment to explore the phenomena in the agricultural sector. Based on the findings, the paper proposes the farmersâ€™ group empowerment strategies such as farmerâ€™s group learning and innovation and information and communication technology (ICT) have a positive influence on improving their income. Keywords: Â Empowerment, farmers group, income, strategy, agriculture, learning, innovation, ICT